Barriers to expand solar photovoltaic energy in Brazil - Queiroz, Jamerson Viegas (2020)
Renewable energy has promoted increasingly diffused propulsions in political, social and organizational environments because of their relevance to future climatic conditions and restrictions on natural resources that threaten environmental impacts. Brazil has enormous potential to exploit renewable energy, especially hotovoltaic solar energy, since it has a daily solar incidence of between 4,500 Wh/m2 and 6,300 Wh/m2. However, the development of this energy in Brazil faces barriers that end up hindering its implementation and expansion. The objective of the research is to identify and measure the impact of these barriers to the expansion of photovoltaic solar energy in Brazil, through the modeling of structural equations. For the development of the article, interviews with managers of the solar energy sector were carried out all over the country